Peripheral Arterial Tonometry (EndoPAT)-measured Endothelial Dysfunction in Migraine with Aura children - Bonuccelli, Alice; Sciarrotta, Claudia; Esposito, Maria Grazia; Bianchi, Vanessa; Miccoli, Mario; Striano, Pasquale; D'angelo, Riccardo; Valiani, Margherita; Randazzo, Emioli; Foiadelli, Thomas; Peroni, Diego; Federico, Giovanni; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background. The association between Migraine with Aura (MA) and vascular disease has been previously reported. We investigated whether pre-clinical vascular alterations, such as Endothelial Dysfunction, are already present in children and adolescents with Migraine with Aura. Methods. We retrospectively enrolled 27 patients having Migraine with Aura, aged9 -18 years, and 31 age matched healthy control subjects to evaluateEndothelial Function by Peripheral Arterial Tonometry. This technique measures finger pulse wave amplitude, before and during reactive hyperaemia, and calculates the Augmentation Index (AI) and the Reactive Hyperaemia Index (RHI). We also set-up an Aura Severity Scale to assess disease severity and its relationship with AI and RHI alterations. Results. Also if the case-control study resulted only partially as significant, we found there is an inversely proportional relationship between the severity of the migraine measured with Aura Severity Scale and the values of the endoscore (a significantly reduced levels of AI (p-value <0,03) and a marginal reduction of RHI levels (p-value <0,07). Conclusion. Further studies should explore the impact of pre-clinical vascular alterations in children and adolescents with Migraine with Aura.